Intersemiotic complementary: The multimodal discourse analysis on tempo magazine covers - Lubis, Malan; Surip, M. (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
Mass media, such as Tempo magazine, is vital in conveying messages through verbal and visual text, especially in criticizing social and political issues. The visual and text elements in the magazine’s cover function as not only just for decoration but also complement each other in conveying the overall message to the reader. This research aims to describe the intersemiotic complementarity of verbal and visual texts on the Tempo magazine (CMT) cover. The data sources of this research were generated from Tempo magazine's January 2023 to September 2023 issues. The research method used was descriptive qualitative. The data were analyzed using Liu Y and O'Halloran's intersemiotic logical relationship theory. The results showed that of the 36 data analyzed, 19 data were additive (52.8%), 8 data were causal effect (consequential) (22.2%), 6 data were comparative (16.7%), and 3 data were temporal (8.3%). In conclusion, the verbal and visual texts on the cover of Tempo magazine complement each other and create a coherent meaning, with additive relations being the most dominant.